A two‐dimensional global simulation study of inductive‐dynamic magnetosphere‐ionosphere coupling. Issue 12 (20th December 2016) - Tu, Jiannan; Song, Paul
Abstract: We present the numerical methods and results of a global two‐dimensional multifluid‐collisional‐Hall magnetohydrodynamic (MHD) simulation model of the ionosphere‐thermosphere system, an extension of our one‐dimensional three‐fluid MHD model. The model solves, self‐consistently, Maxwell's equations, continuity, momentum, and energy equations for multiple ion and neutral species incorporating photochemistry, collisions among the electron, ion and neutral species, and various heating sources in the energy equations. The inductive‐dynamic approach (solving self‐consistently Faraday's law and retaining inertia terms in the plasma momentum equations) used in the model retains all possible MHD waves, thus providing faithful physical explanation (not merely description) of the magnetosphere‐ionosphere/thermosphere (M‐IT) coupling. In the present study, we simulate the dawn‐dusk cross‐polar cap dynamic responses of the ionosphere to imposed magnetospheric convection. It is shown that the convection velocity at the top boundary launches velocity, magnetic, and electric perturbations propagating with the Alfvén speed toward the bottom of the ionosphere. Within the system, the waves experience reflection, penetration, and rereflection because of the inhomogeneity of the plasma conditions. The reflection of the Alfvén waves may cause overshoot (stronger than the imposed magnetospheric convection) of the plasma velocity in some regions. The simulation demonstrates dynamic propagation of the field‐aligned currents and ionospheric electric field carried by the Alfvén waves, as well as formation of closure horizontal currents (Pedersen currents in the E region), indicating that in the dynamic stage the M‐I coupling is via the Alfvén waves instead of field‐aligned currents or electric field mapping as described in convectional M‐I coupling models. Key Points: A 2‐D global inductive‐dynamic ionosphere/thermosphere model is developed Simulation study shows dynamic propagation of the electric field and field‐aligned currents and formation of the Pedersen currents It is shown that during dynamic stage, the M‐I coupling is via the Alfven waves instead of field‐aligned currents or electric field mapping